Engineering reversible cell–cell interactions using enzymatically lipidated chemically self-assembled nanorings. Issue 1 (4th November 2020) - Wang, Yiao; Kilic, Ozgun; Csizmar, Clifford M.; Ashok, Sudhat; Hougland, James L.; Distefano, Mark D.; Wagner, Carston R.
Abstract : Multicellular biology is dependent on the control of cell-cell interactions. The prenylated antigen-targeted CSANs provide a general approach for the regulation of specific cell-cell interactions and will be valuable for a plethora of fundamental and therapeutic applications. Abstract : Multicellular biology is dependent on the control of cell–cell interactions. These concepts have begun to be exploited for engineering of cell-based therapies. Herein, we detail the use of a multivalent lipidated scaffold for the rapid and reversible manipulation of cell–cell interactions. Chemically self-assembled nanorings (CSANs) are formed via the oligomerization of bivalent dihydrofolate reductase (DHFR 2 ) fusion proteins using a chemical dimerizer, bis-methotrexate. With targeting proteins fused onto the DHFR 2 monomers, the CSANs can target specific cellular antigens. Here, anti-EGFR or anti-EpCAM fibronectin-DHFR 2 monomers incorporating a CAAX-box sequence were enzymatically prenylated, then assembled into the corresponding CSANs. Both farnesylated and geranylgeranylated CSANs efficiently modified the cell surface of lymphocytes and remained bound to the cell surface with a half-life of >3 days. Co-localization studies revealed a preference for the prenylated nanorings to associate with lipid rafts. The presence of antigen targeting elements in these bifunctional constructs enabled them to specifically interact with target cells while treatment with trimethoprim resulted in rapid CSAN disassembly and termination of the cell–cell interactions. Hence, we were able to determine that activated PBMCs modified with the prenylated CSANs caused irreversible selective cytotoxicity toward EGFR-expressing cells within 2 hours without direct engagement of CD3. The ability to disassemble these nanostructures in a temporally controlled manner provides a unique platform for studying cell–cell interactions and T cell-mediated cytotoxicity. Overall, antigen-targeted prenylated CSANs provide a general approach for the regulation of specific cell–cell interactions and will be valuable for a plethora of fundamental and therapeutic applications.